Isolation and Cloning of ABCC2 Gene from Rasbora Sarawakensis - Mohd Zulfazli, Moktar (Universiti Malaysia Sarawak (UNIMAS), 2015)
ABC genes encode ABC transporter proteins which have a significant function in transporting molecules across the cells. ABCC2 gene involve in the multidrug resistance associated protein mechanism where loss of such gene has been implicated with the Dubin-Johnson syndrome (DJS) which caused by impaired of methotrexate elimination. The purpose of this study is to identify the expression of ABCC2 gene in Rasbora sarawakensis, then to clone it into pGEM-T easy vector. Total RNA was extracted from whole fish homogenate via Tri reagent and phenol chloroform precipitation. The cDNA generated from reverse transcription and was amplified with PCR using degenerate primers targeting the conserved region of the gene. The PCR produced an approximately 696 bp amplicon which then was cloned into pGEM-T easy vector. Transformation was performed using in house prepared E.coli XL1-blue competent cells which produced an efficiency of 1.28×10^6 transformants/μg. Afterward, white colonies run on colony PCR and its revealed the presence of insert. Moreover, further confirmation was conducted through NotI restriction digestion which shown two discreet bands. Subsequently, the plasmid that was obtained from plasmid mini preparation was sent for sequencing and the result was corroborated by using BLAST which then show the highest similarity with D. rerio ABCC2 transcript. Based on this study, the future expression identification and functional analysis of this gene in multixenobiotic mechanism can be carried out, thus establishing the R. sarawakensis as the ecotoxicology model for studying water condition in Sarawak.